Las finanzas personales y su importancia en la toma de decisiones en los hogares del cantón Chaguarpamba - Encalada Ramirez, Arelis Carolayn (2022)
Financial management is a determining factor in the structure and state of the family economy, it is the key to having a successful economic life since if there is good control of the things, it can make significant progress; For this reason, the purpose of this research is to analyze personal finances and its importance in decision-making in households in the Chaguarpamba canton. A descriptive methodology was obtained and the research approach was mixed. In addition, the inductive, synthetic, and analytical methods were applied. The data collection instrument was the survey and the sample consisted of 228 people, whose results indicate that the inhabitants have a lack of knowledge of financial issues, and do not plan for the management of their economic resources, for this reason, there are errors in decision making. It is concluded that personal finances are the set of decisions that are made over some time by a family to be able to satisfy all their present and future needs. Therefore, it is necessary to instruct people in financial education, since if they improve their level of knowledge and financial planning, they will also improve their quality of life.